IDENTIFIKASI KONTAMINASI Salmonella Typhi BERDASARKAN AMPLIFIKASI GEN fliC PADA CINCAU DI PASAR TRADISIONAL DAN MINIMARKET KOTA SEMARANG - Ernanto, Aditya Rahman; Palimbongan, Junita Rensa; Manufandu, Anjar Richardo; Darmawati, Sri (Jurnal Teknologi Laboratorium, 2020)
Grass-jelly is one of the most popular plants consumed by people in various forms of beverage mix because it is easy to gets in traditional markets. Microorganism contamination can occur in grass-jelly due to several factors such as water for processing, equipments, processing facilities and from people who did the process. Contamination can cause various diseases, one of those is typhoid fever by Salmonella typhi. The purpose of this study was to detect S. typhi in grass-jelly based on molecular detection by amplification of the fliC gene using PCR. Steps of the methods were DNA extraction from grass-jelly samples, genomic DNA quality testing, amplification of fliC gene and agarose electrophoresis. Validation was done by culture methods on SSA media and biochemical testing. The fliC gene amplification results in grass-jelly samples (A1, A2, B1, B2, C1 and C3) showed the DNA fragments size about 1500 bp. Colony and biochemical characters isolates Peterongan were lead to S. typhi, whereas another isolate were another Salmonella spp. The conclusion of this study was that grass-jelly samples from Peterongan market in Semarang were positively contaminated by S. typhi and isolate from Pedurungan and minimarket were another Salmonella spp. Molecular-based food testing is fast enough and accurate for detecting types of bacterial contaminants but amplification of fliC gene cannot specific for S. typhi.